Enhancing Primary Schoolchildren’s Autonomy and Interest towards Reading through Inquiry-based Activities and Digital Applications (A Case of Georgian Private School) - Irina Chikovani; Ekaterine Pipia (European Scientific Journal, ESJ, 2022)
Over the last century language teaching methods have undergone fundamental changes. A different set of approaches has appeared in response to the ineffectiveness of traditional teaching methods. As traditional approaches are not designed to pursue students’ interests and do not encourage them to cooperate in self-directed learning, there is an urgent need to develop more effective teaching and learning approaches for 21st-century learners. Nowadays, teacher-centered education gives the way to more student-centered approaches, where the main goal of learning is to nourish interest in students and give them an opportunity to inquire and master learning in a more meaningful way. As technology-assisted education has become an indispensable and challenging part of student-centered education, it has become absolutely vital for teachers to enhance the integration of technology into their classrooms. Inquiry-based English language teaching through digital applications is among the most contemporary teaching approaches, which perfectly corresponds to the 21st-century demands while enhancing autonomy and fostering students’ reading interest. Considering the urgency of integrating contemporary teaching methods in English as a Foreign Language (EFL) class, the objective of the presented study has been shaped to outline the impact of inquiry-based English language teaching through digital applications on primary learners’ autonomy and interest development in one of the Georgian private schools. A quantitative method was applied to the present study in order to compare pre and post-experimental questionnaire results and measure primary schoolchildren’s autonomy level, curiosity, and interest in reading through digital applications before and after the experiment. The learning processes of the experimental and control groups were compared. The obtained data has been analyzed using SPSS to compare the survey results. The quantitative study has revealed that the 21st-century generation positively responds to contemporary teaching methods and inquiry-based teaching through digital applications has proved to be effective. Based on the research findings, eBooks and digital applications are reasonable resources to be utilized in EFL reading lessons as learning only with the help of traditional books appears to be boring for students. Based on the study results, it is obvious that working on electronic texts through inquiry-based approaches has assisted students in completely changing their negative attitudes toward reading and increased engagement and autonomy. Consequently, because of the decreasing interest in reading through traditional books, there is a need of promoting more student-centered teaching practices and increase technology integration in the teaching and learning process.